PRODUCTION OF FISHING CAPTURE FISHERIES KURAU NETWORK IN THE ALAH AIR LAUT VILLAGE DISTRICTS TEBING TINGGI, MERANTI ISLANDS - Suheryanto Oktafianus Simanjorang; Arthur Brown; Ronald Mangasi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research has been carried out in July 2019 until August 2019, in Alah Air Village, Tebing Tinggi District, Meranti Islands. The purpose of this study is to determine the general construction of the kurau net fishing gear, know the productivity of the kurau net fishing gear, determine the catch season index, describe the number of catches and target species (main target), analyze the length of the caught fish. The method used during this research is a survey method bydescribing directlythe work process of the kurau net fishing gear and participating in the operation process of thekurau net fishing gear.Based on the results of the production of Kurau nets for 5 years shows that efforts to catch kurau fish and the production of kurau fish experience fluctuations every year. In the period starting from 2015-2019, 2017 was the year of the highest production of kurau nets with the number of catches of kurau nets with a total of 7205 kg / year, and the highest catch occurred in March, which was 867.7 kg while the lowest catch occurred in July that is 166.6 kg. Based on the calculation of the Catching Season Index, it is known in October to April that the catches are abundant. In those months fishing is best done and the peak season is in January. In May to September the fish catch is very small, this month is a bad time for fishing.Keywords: Kurau Net, Productivity, Fluctuation, Catching Season Index